Perencanaan Persediaan Bahan Baku Pakan Ternak Broiler XYZ Dengan Metode MRP Di PT Cj Feed And Care Indonesia (Jombang Factory) - Rochmatulloh, Andri; Mayasari, Andhika; Sumarsono (Teknik Industri, Fakultas Teknik, Universitas Hasyim Asy'ari, 2024)
PT CJ Feed and Care Indonesia (Jombang Factory) is a company operating in the animal feed industry. Improper production planning causes problems in managing raw materials, and often the stock of raw materials for production is overstocked, resulting in warehouse rental costs. In the period January 2024 to April 2024, 30,545 tons of raw materials were recorded in the rental warehouse, and storage rental costs amounted to 675 million. The purpose of this research is to determine the production volume of XYZ Broiler products based on past sales estimates. And to plan raw material supplies for the production of XYZ Broiler products using the Material Requirement Planning (MRP) method with the Economic Order Quantity (EOQ) technique. Based on sales data, the Decomposition method is the best forecasting method because it has the lowest MAPE, MAD and MSD values. Therefore, we can conclude that sales for the last 4 months, namely January to April 2024, were 4,498, 4,303, 5,582 and 3,884 tons. The final process for obtaining data on raw material requirements is creating an MRP report using the EOQ technique. With this MRP method, the company can provide raw materials according to sales demand so that it does not need to rent an external warehouse to store excess raw materials and can save 675 million from the cost of renting an external warehouse for 4 months and Rp. 381,812,500,000 from the cost of purchasing Soya Bean M eal (SBM) materials. overstock.